Almanac of famous people(formerly biography almanac) - Stetler, Susan L. (Detroit : Gale Research Inc., 1989)
A dictionary and index of thousands of well-known individuals throughout history.
Vol 3 indexes.
Keywords: Biography -- Periodicals; Biography -- Indexes -- Periodicals